Unveiling the Relationship Between Sea Surface Hydrographic Patterns and Tuna Larval Distribution in the Central Mediterranean Sea - Russo, Stefania; Torri, Marco; Patti, Bernardo; Reglero, Patricia; Álvarez-Berastegui, Diego; Cuttitta, Angela; Sarà, Gianluca (Frontiers in Marine Science, 2021)
Thunnus thynnus, (Atlantic Bluefin tuna, ABT) and other tuna species reproduce in the Mediterranean Sea during the summer period. Despite the Central Mediterranean Sea and the Strait of Sicily in particular, being a key spawning site for many tuna species, little is known on the effects of the oceanographic variability on their larval distribution in this area. Using historical larval collections from seven annual surveys (2010-2016) and in-situ environmental measurements, we modeled abundance and presence-absence to examine the relationship with environmental variability for three tuna species (ABT, Bullet tuna and Albacore). The results revealed that most tuna larvae for the three species, were in the Easternmost part of the study area, South of Capo Passero. This area is characterized by a stable saline front and warmer nutrient-poor waters and has different environmental conditions, compared to the surrounding areas. The models used to investigate presence-absence and abundance of the three species showed that ABT was the most abundant, followed by Bullet tuna and Albacore. The presence and abundance data collected is comparable to other spawning areas in the Mediterranean. Regarding the biological and physical parameters, our results suggest that temperature, salinity, and day of the year are the key factors for understanding the ecological mechanisms and geographical distribution of these species in this area. Temperature affects the presence of ABT larvae and salinity which, with a physical barrier effect, is a key factor for the presence-absence of Bullet and Albacore and for Albacore abundance.